Identification of the Epidemiological Characteristics of Chronic Fatigue Syndrome Among Tikrit University Students - Areej Muthanna Noaman; Nisreen Mohammed Ibraheem; Athraa Essa Ahmed; Junaid Mohammed Ameen Alli (Academic Journal of Clinicians, 2025)
Background: chronic fatigue syndrome ,defined as the condition in which the person have persistent fatigue accompanied by other specific symptoms for a minimum of six months not due to ongoing exertion not relieved by rest and not caused by other medical conditions. Objectives: To find the frequency of Chronic Fatigue Syndrome and epidemiological characteristics among Tikrit University students, as well as identifying the relationship between chronic fatigue syndrome and history of physical and mental stress and history of smoking. Subjects and Methods: A cross-sectional study has been conducted on 260 students on different colleges of Tikrit University/Iraq. The study spanned between January 1st to March 1st 2023. All the participants have been given a self- explanatory questionnaire related to chronic fatigue syndrome (CFS) diagnostic criteria. Results: Chronic fatigue syndrome was found to be frequent among Tikrit University students with overall frequency of (33.8%). The females are more affected than males by this syndrome. About (42%) of persons with have history of physical stress and (9%) of them suffered from mental stress. Concerning the age of patients, it is found that frequency of Chronic Fatigue Syndrome increases in the age group of 18-20 years old. Although, most studies have not mentioned the relation between smoking and chronic fatigue syndrome, in this study Chronic Fatigue Syndrome among smokers show a frequency of (39.5%). Concerning the symptoms of this syndrome we found that fatigue and sleep disturbance were the major symptoms of frequency (100%) also poor memory account (70.4%) and photosensitivity (37.84%), (63.36%) have intestinal disturbance, (48.4%) have poor appetite, and (68.64%) have headache and this agree with previous studies. There was a variation between colleges in number of persons affected with Chronic fatigue syndrome most of them were from college of Literature (17%), college of Biology (13.6%), college of Medicine (12.5%), while the college of Pharmacy and Agriculture show the least frequency (4.5%). Conclusion: There is a relatively high percentage (33.8%) of Tikrit University students with Chronic Fatigue Syndrome, which is more frequent in females. This syndrome is more frequent in the age group of (18-20) years old students. Half of those affected by this syndrome have a history of physical and/or mental stress.